Low‐Dose Irradiation Enhances Gene Targeting in Human Pluripotent Stem Cells. (16th July 2015) - Hatada, Seigo; Subramanian, Aparna; Mandefro, Berhan; Ren, Songyang; Kim, Ho Won; Tang, Jie; Funari, Vincent; Baloh, Robert H.; Sareen, Dhruv; Arumugaswami, Vaithilingaraja; Svendsen, Clive N.
Abstract : Human pluripotent stem cells (hPSCs) are being used for both disease modeling and cell therapy; however, efficient homologous recombination (HR) is often crucial to develop isogenic control or reporter lines. This study showed that limited low‐dose irradiation significantly enhanced HR frequency. This simple method allows higher throughput of new, targeted hPSC lines that are crucial to expand the use of disease modeling and to develop novel avenues of cell therapy. Abstract : Human pluripotent stem cells (hPSCs) are now being used for both disease modeling and cell therapy; however, efficient homologous recombination (HR) is often crucial to develop isogenic control or reporter lines. We showed that limited low‐dose irradiation (LDI) using either γ‐ray or x‐ray exposure (0.4 Gy) significantly enhanced HR frequency, possibly through induction of DNA repair/recombination machinery including ataxia‐telangiectasia mutated, histone H2A.X and RAD51 proteins. LDI could also increase HR efficiency by more than 30‐fold when combined with the targeting tools zinc finger nucleases, transcription activator‐like effector nucleases, and clustered regularly interspaced short palindromic repeats. Whole‐exome sequencing confirmed that the LDI administered to hPSCs did not induce gross genomic alterations or affect cellular viability. Irradiated and targeted lines were karyotypically normal and made all differentiated lineages that continued to express green fluorescent protein targeted at the AAVS1 locus. This simple method allows higher throughput of new, targeted hPSC lines that are crucial to expand the use of disease modeling and to develop novel avenues of cell therapy. Significance: The simple and relevant technique described in this report uses a low level of radiation to increase desired gene modifications in human pluripotent stem cells by an order of magnitude. This higher efficiency permits greater throughput with reduced time and cost. The low level of radiation also greatly increased the recombination frequency when combined with developed engineered nucleases. Critically, the radiation did not lead to increases in DNA mutations or to reductions in overall cellular viability. This novel technique enables not only the rapid production of disease models using human stem cells but also the possibility of treating genetically based diseases by correcting patient‐derived cells.